Analysis of the Effect of Ability and Motivation on the Performance of Counter Employees at the Social Service of Medan City in 2020-2022 - Nur Nabilllah; Sri Surdiarti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This research was conducted on Medan City Social Service Employees with the aim of analyzing the influence of variables on the performance and motivation of Medan City Social Service Employees. The purpose of this study was to determine the effect of ability and motivation on the performance of Medan City Social Service Employees. Sampling was carried out using the census method with the entire population as respondents, namely 23 people. The analytical method used is descriptive qualitative method, and data collection techniques are carried out using interviews and questionnaires to all respondents. From the results of the study, it was found that the motivation variable was the most dominant factor, with an average of 3.98 higher than the average capacity variable of 3.64. The suggestion that the writer can give is that the Medan City Social Service should pay more attention to the work ability of employees by increasing the implementation of technical training and employee motivation to pay attention and demand more productivity so that each job can be completed optimally. , as well as employee evaluations must be carried out carefully to provide a higher quality of employee performance.